Glass tiber's of triangular cross-sections with metal loading on one or more sides - A comparative modal study - Ojha S.P.; Choudhury P.K.; Khastgir P. (My University, 2025)
Using the point-matching method a comparative study has been made of the propagation characteristics of a triangular-cored glass fiber waveguide which is loaded on one or two sides with a highly conducting substance, the remaining side/sides being adjacent to a dielectric material of lower refractive index than that of the core. © 1991 SPIE. All rights reserved.